Efforts to Overcome Poverty Through Integrated Education and Business Skills As a Form of National Defense - Afifah, Rifdah; Wahyudi, Slamet Tri (Rechtsvinding, 2025)
Poverty in Indonesia, affecting almost a quarter of the total population, or approximately 23.85 million people, is a structural issue that has a reciprocal relationship with low educational quality, creating a vicious cycle that impedes national progress. This condition is exacerbated by educational disparities, as reflected in Indonesia's low global ranking, and the state's failure to realize the mandate of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) to enlighten the nation through the effective allocation of 20% of the State Budget (APBN). The failure of the poor to acquire sufficient skills and critical thinking through education directly impacts national Human Resources (HR) quality and traps the country in the middle-income trap (mid-life crisis). This study aims to analyze the factors contributing to high poverty and low education, and to formulate policies that can integrate education and business skills as a fundamental effort in national defense (Bela Negara). This research employs the Normative Legal Research method using the statutory approach and the Conceptual Approach. The findings indicate that structural poverty and the state's failure to holistically implement the welfare state concept, including the inefficiency in allocating the 20% education budget, are the main factors perpetuating poverty. The proposed solution is an integrated policy that not only relies on social assistance and scholarships (KIP, KJMU) but also demands macro-economic reforms focused on inclusive growth and the development of education relevant to business skills as a permanent solution.